Partial Replacement of Soybean Cake with Amaranth us spinosus Leaf Meal in the Diet of Nile Tilapia ( Oreochromis niloticus) (Biological Sciences - PJSIR, 2007)
. The study, designed to assess the potentials of oven dried Amaranth us spinosus leaf meal as parti a l replacement for soybean cake i n the diet of Nile Ti lapia, revealed no significant di fference (P> 0.05) in feed and protei n i ntake. Fish fed on Amaranthus spinosus leaf meal diets had significant (P